Penerapan Prinsip Kehati-Hatian Notaris Dalam Mengenal Para Penghadap - Fikri Ariesta Rahman (Universitas Islam Indonesia, 2018)
The problem that is discussed in this research is the implementation of the precautionary principle of the Notary in knowing the applicant; and the legal consequences of an authentic deed which is made by the notary who has not applied the precautionary principle in knowing the applicant. This research uses a juridical-empirical approach, by analyzing a statute that applies to be used as a basis for solving problems. The informant is a notary in Yogyakarta City who is still active in the Regional Supervisory Council and Central Supervisory Council. The results of this study explain that the Notary in applying the Precautionary Principle begins with ensuring and checking the formal truth of the applicant. if it is deemed insufficient, then the notary should seek material truth, in order to achieve the goal of the precautionary principle in getting to know the parties and minimize the possibility of problems in the future. Legal consequences if the notary does not apply the precautionary principle would be, if a mistake comes from the parties towards the deed, then the deed can be degraded to a deed under the hand. If the notary who is guilty, then he or she can be held liable either administratively, civil or criminal.